STUDYING THE SECONDARY STRUCTURE OF ACCESSION NUMBER USING CETD MATRIX - Dutta, Anamika (Journal of process management and new technologies, 2016)
This paper, we have tried to analyze about the Secondary Structure of nucleotide sequences of rice. The data have been collected from NCBI (National Centre for Biotechnology Information) using Nucleotide as data base. All the programs were developed using R programming language using “sequinr” package. Here, we have used CETD matrix method to study the prediction. The conclusions are drawn accordingly.